Subendometrial resistence and pulsatility index assessment of endometrial receptivity in assisted reproductive technology cycles - Silva Martins, R.; Helio Oliani, A.; Vaz Oliani, D.; Martinez de Oliveira, J. (Reproductive biology and endocrinology, 2019)
To evaluate Subendometrial and Uterine artery resistance and pulsatility index continuous analysis as a predictor of Endometrial receptivity in Assisted Reproductive Technology (ART) Cycles. Serial 2D transvaginal coloured power doppler ultrasound performed in women on ART cycle to evaluate a pattern that better predicts implantation rates. One hundred sixty-nine subjects on a prospective case control study were assessed. Uterine artery and Subendometrial resistance and pulsatility index was performed to all subjects at baseline (prior to ovarian controlled stimulation), at day 6, 8 and 10 of controlled ovarian stimulation, at trigger day and at embryo transfer day. Also the ratio of fluxometric parameters between Subendometrial blood flow and uterine artery was measured. No statistical difference was noted between two groups in terms of demographics and ART procedures and scores. Uterine artery resistance and pulsatility index showed statistical difference between the two groups (implantation versus non-implantation group). Also statistical significance was obtained between two groups in terms of Subendometrial vascularization. Ratio between Subendometrial and Uterine artery showed lower values of fluxometric parameters in all range for the Subendometrial territory. Serial Subendometrial and Uterine artery fluxometry may be a useful tool for clinicians in predicting endometrial receptivity enhancing elective embryo transfers in the same ART cycle.